Analisis Kelayakan Usaha Rumah Makan “Sederhana” Ditinjau dari Aspek Pasar, Operasional, dan Finansial - Handayani, Hanny; Sawalni, Sawalni; Nasywa, Nisrina; Iskandar, Dimas Satria; Khairunnisa, Fitri Nabila; Almuhajir, Hizkia Ihza; Hermawansyah, Febby Setya; Sasmita, Erick Surya (INDO PUBLISHING, 2026)
This study aims to analyze the business feasibility of Warung Nasi “Sederhana” in terms of market, operational, and financial aspects. The research method employed is a descriptive quantitative approach, with data collected through interviews and direct observation of the business owner. Financial feasibility analysis was conducted using Payback Period, Net Present Value, Internal Rate of Return, Benefit Cost Ratio, Break Even Point, and sensitivity analysis methods. The results indicate that Warung Nasi “Sederhana” has a relatively short payback period, a positive NPV value, an IRR higher than the discount rate, and a B/C ratio greater than one. Furthermore, the BEP analysis shows that the sales level has exceeded the break-even point. Sensitivity analysis reveals that the business remains feasible under reasonable revenue declines but is sensitive to increases in operating costs. Therefore, it can be concluded that Warung Nasi “Sederhana” is feasible to operate and develop.